OP66 Multilevel influences on overweight and obesity in 8–11 year old Irish children: findings from the Cork Children's Lifestyle Study (CCLaS). (2nd September 2014) - Keane, E; Perry, IJ; Kearney, PM; Harrington, JM
Abstract : Background: Globally, the high prevalence of childhood obesity is recognised as a significant public health problem associated with adverse health consequences. Thus, a comprehensive understanding of this multifaceted problem is necessary to inform effective public health strategies. We aim to assess modifiable individual factors associated with childhood overweight and obesity whilst considering broader contextual factors including the home and local environment Methods: CCLaS is a cross sectional survey of 1075 children aged 8–11 years in Cork, Ireland. Schools were recruited from Cork City using probability proportionate to size sampling. Complete sampling recruited schools from one rural area of Cork County. Child height and weight were measured by trained researchers using standard methods. International Obesity Taskforce definitions for body mass index were used to define obesity. Children wore wrist-worn Geneactiv accelerometers for 7 days and raw accelerometer data was used to categorise moderate-to-vigorous physical activity (MVPA). Information on diet and lifestyle were reported separately by children (local playground facilities, neighbourhood safety), parents (child sleep, screen time, child and family eating patterns, self-reported parent height and weight, parent education) and principals (school environment) in questionnaires. Age and sex adjusted logistic regression was conducted for each independent variable, whilst accounting for the clustering of children within schools. All significant variables were then included in a multivariate logistic regression. Results: The prevalence of overweight was 20.0% (95% CI 17.6–22.4) and obesity 5.3% (95% CI 4.0–6.7), with more girls overweight or obese than boys (p = 0.1). The age and sex adjusted regression models indicated that inadequate sleep time, total screen time, not meeting 60 min MVPA/day, skipping breakfast, no fruit consumption, high family consumption of takeaway food, lower levels of maternal education and maternal overweight/obesity were all associated with a significantly increased odds of childhood overweight/obesity. School disadvantaged status, local playground facilities and neighbourhood safety did not significantly increase the odds of overweight/obesity. In the fully adjusted model, inadequate sleep time (OR 2.2, 95% CI 1.4–3.5), not meeting 60 minutes MVPA/day (OR 2.2, 95% CI 1.5–3.2), lower levels of maternal education and maternal overweight/obesity (OR 2.1, 95% CI 1.4–3.0) remained statistically significant. Conclusion: Individual and family factors appear most strongly associated with childhood overweight/obesity in Ireland. However, from a public health perspective targeting change at an environmental level may be the most effective means of providing population based obesity interventions. Better measures on wider contextual social, economic and cultural factors are needed to better understand multilevel influences on obesity.